Development of a framework for knowledge mobilisation and impact competencies. (26th November 2018) - Bayley, Julie Elizabeth; Phipps, David; Batac, Monica; Stevens, Ed
Abstract : For research to translate into impact, knowledge must be effectively mobilised beyond the academic domain. However, there is little consensus on the competencies (skills) required. This paper describes the development of a competency framework. Four existing knowledge broker frameworks were synthesised through a process of (1) extraction, (2) categorisation, (3) cleaning and (4) re-categorisation. A final set of 80 distinct, actively-phrased competencies in 11 categories was produced. This paper provides the first comprehensive framework for professional competences for impact beyond commercialisation. The potential applications, implications for competencies and associated competence alongside further research are discussed.